Wnt and extraocular muscle sparing in amyotrophic lateral sclerosis - McLoon, Linda K; Harandi, Vahid M; Brännström, Thomas; Andersen, Peter M; Liu, Jing-Xia (Investigative ophthalmology & visual science, 2014)
The extraocular muscles (EOM) and their motor neurons are spared in amyotrophic lateral sclerosis (ALS). In limb muscle, axon retraction from the neuromuscular junctions occurs early in the disease. Wnts, a conserved family of secreted signaling molecules, play a critical role in neuromuscular junction formation. This is the first study to examine Wnt signaling for its potential involvement in maintenance of normal morphology in EOM in ALS. Extraocular muscle and limb muscle axons, neuromuscular junctions, and myofibers from control, aging, and ALS subjects and the SOD1(G93A) mouse model of ALS were quantified for their expression of Wnt1, Wnt3a, Wnt5a, Wnt7a, and β-catenin. All four Wnt isoforms were expressed in most axon profiles in all human EOM. Significantly fewer were positive for Wnt1, Wnt3a, and Wnt7a in the human limb muscles. Similar differential patterns in Wnt myofiber expression were also seen except in the case of Wnt7a, where expression was elevated. In the SOD1(G93A) mouse, all four Wnt isoforms were significantly decreased in the neuromuscular junctions at the terminal stage compared to values in age-matched controls. β-Catenin was activated in a subset of myofibers in EOM and limb muscle in all subjects. The differences in expression of Wnts in EOM and limb muscle, particularly at the neuromuscular junction level, suggest that they play a role in the pathophysiology of ALS. Collectively, the data support a role for signaling of Wnts in the preservation of the EOM in ALS and their dysregulation and the subsequent development of pathology in the ALS limb muscles.